2022
DOI: 10.1002/nop2.1419
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and sleep quality in patients with arteriosclerotic obliterans: The mediating roles of psychological flexibility

Abstract: Aim The aim of the study was to investigate the effect of perceived social support (PSS) on sleep quality in arteriosclerotic obliterans patients in China and examined whether psychological flexibility (PF) has a mediating effect between PSS and sleep quality. Design A cross‐sectional survey. Methods A cross‐sectional study was conducted between September 2020 and December 2021 on 172 patients with atherosclerotic obliterans recruited from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Herbal fumigation and washing act locally, enhancing joint flexibility, muscle relaxation, circulation, and reducing complications [22,23]. Nursing's multifaceted approach, coupled with educational programs, reduces fear and anxiety, enhances patient engagement, and optimizes therapeutic outcomes [24]. In this study, the experimental group enjoyed higher nursing satisfaction and experienced fewer complications than the control group, indicating the safety and effectiveness of herbal fumigation.…”
Section: Discussionmentioning
confidence: 63%
“…Herbal fumigation and washing act locally, enhancing joint flexibility, muscle relaxation, circulation, and reducing complications [22,23]. Nursing's multifaceted approach, coupled with educational programs, reduces fear and anxiety, enhances patient engagement, and optimizes therapeutic outcomes [24]. In this study, the experimental group enjoyed higher nursing satisfaction and experienced fewer complications than the control group, indicating the safety and effectiveness of herbal fumigation.…”
Section: Discussionmentioning
confidence: 63%
“…A survey showed that patients are prone to nervousness, anxiety, and irritability during dialysis. These negative emotions will cause or worsen other symptoms, such as fatigue or sleep disorder [ 56 , 57 ], and cause an immense disease burden for patients. At the same time, these emotions will decrease confidence in fighting the disease and the self-worth of patients [ 58 ], directly affecting dialysis quality and even increasing the mortality rate [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high symptom burden tends to cause anxiety, sadness, nervousness, and depression. These negative emotions will accelerate heart rate, increase blood pressure, and cause or worsen other symptoms, such as fatigue and sleep disorder [ 56 , 57 ]. This shows that negative emotions play a bridging role in the occurrence and progression of symptoms during dialysis in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety is the most common adverse emotional reaction, with an incidence of 40.0% to 53.4% in MHD patients 9 . The study has shown a negative correlation between anxiety and sleep quality, indicating that anxiety is one of the factors contributing to the decline in sleep quality and the development of sleep disorders in these patients 10 .…”
Section: Introductionmentioning
confidence: 86%